Modeling of reverberation chamber using FMM-accelerated hybrid integral equation - Zhao, Huapeng (2013)
Iterative solvers suffer from slow convergence in modeling a highly resonant reverberation chamber (RC). In this paper, a hybrid integral equation accelerated by the fast multiple method (FMM) is utilized to model RC and to improve the convergence behavior. The hybrid method's performance is studied and the error introduced by the FMM is analyzed. It is found that the truncation error of multi-pole expansion can be significant in some cases, which may become critical in modeling highly resonant structures like the RC.